Homochiral Asymmetric-Shaped Electron-Transporting Materials for Efficient Non-Fullerene Perovskite Solar Cells - Jung, Su Kyo; Heo, Jin Hyuck; Lee, Dae Woon; Lee, Seung Heon; Lee, Seung Chul; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Kim, Jong H.; Im, Sang Hyuk; Kwon, O. Pil (ChemSusChem, 2019)
A design strategy is proposed for electron-transporting materials (ETMs) with homochiral asymmetric-shaped groups for highly efficient non-fullerene perovskite solar cells (PSCs). The electron transporting N,N′-bis[(R)-1-phenylethyl]naphthalene-1,4,5,8-tetracarboxylic diimide (NDI-PhE) consists of two asymmetric-shaped chiral (R)-1-phenylethyl (PhE) groups that act as solubilizing groups by reducing molecular symmetry and increasing the free volume. NDI-PhE exhibits excellent film-forming ability with high solubility in various organic solvents [about two times higher solubility than the widely used fullerene-based phenyl-C 61 -butyric acid methyl ester (PCBM) in o-dichlorobenzene]. NDI-PhE ETM-based inverted PSCs exhibit very high power conversion efficiencies (PCE) of up to 20.5 % with an average PCE of 18.74±0.95 %, which are higher than those of PCBM ETM-based PSCs. The high PCE of NDI-PhE ETM-based PSCs may be attributed to good film-forming abilities and to three-dimensional isotropic electron transporting capabilities. Therefore, introducing homochiral asymmetric-shaped groups onto charge-transporting materials is a good strategy for achieving high device performance.
Keywords: Charge transporting; Device performance; Electron transport; Electron transporting; Electron transporting materials; Film-forming abilities; Good film forming ability; High power conversion; electron transport; energy conversion; perovskites; solar cells